Ogilvijev sindrom kod COVID-19 pacijenta sa upalom pluća, apsolutnom tahiaritmijom i srčanom slabošću: prikaz slučaja - Matković, Zoran; Đekić Matković, Nataša (Scripta Medica, 2021)
The COVID-19 pandemic has recently spread worldwide presenting primarily in form of pneumonia. Gastrointestinal manifestations such as nausea, vomiting, diarrhoea and abdominal pain are less common than respiratory symptoms. However, critically ill patients may develop digestive complications including acute pseudo-obstruction of colon - Ogilvie syndrome. Gastrointestinal symptoms can manifest before the onset of typical respiratory symptoms. Common mucosal immune response underly both-pulmonary and gastrointestinal manifestations (high expression of angiotensin-converting enzyme 2 receptors). This article described a 75-year old female patient who arise Ogilvie syndrome during viral bilateral pneumonia induced by COVID-19. Patient also had an absolute tachyarrhythmia and hearth failure. Diameter of caecum, ascending and transverse colon was 12 to 14 cm. The walls of this segment of large bowel were deserosed, with threatening perforation. Right colectomy was performed. Nine days after the surgery, despite all therapeutic measures taken, there was a fatal outcome due to pulmonary thromboembolisation.
Keywords: Ogilvie sindrom; COVID-19; Upala pluća; Srčano popuštanje; Gastrointestinalne manifestacije